2014
DOI: 10.1002/ejic.201402001
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria‐Targeted Photoinduced Anticancer Activity of Oxidovanadium(IV) Complexes of Curcumin in Visible Light

Abstract: Oxidovanadium(IV) complexes [VO(py-aebmz)(B)]Cl (1, 2)and [VO(napth-py-aebmz)(cur)]Cl [3; py-aebmz = 2-(1Hbenzimidazol-2-yl)-N-(pyridin-2-ylmethylene)ethanamine, HB = acetylacetone (Hacac, 1) and curcumin (Hcur, 2), napth-py-aebmz = naphthalimide conjugated to py-aebmz ] have been prepared, characterized and their photoinduced DNA cleavage activities and photocytotoxicities studied. Complexes 1-3 each exhibited an irreversible cyclic voltammetric response of the V IV /V III redox couple at around [a]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 63 publications
1
22
0
1
Order By: Relevance
“…Apoptosis damages the mitochondrial cells and decreases the membrane potential . Flow cytometry was used to measure mitochondrial membrane potential in MCF‐7 cells using the JC‐1 (tetraethylbenzimidazolylcarbocyanine iodide) dye for complexes 1 – 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Apoptosis damages the mitochondrial cells and decreases the membrane potential . Flow cytometry was used to measure mitochondrial membrane potential in MCF‐7 cells using the JC‐1 (tetraethylbenzimidazolylcarbocyanine iodide) dye for complexes 1 – 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Senyawa kurkumin memiliki keterbatasan, yaitu bersifat tidak stabil, hal ini terjadi akibat dari gugus β-diketon dalam kurkumin yang rentan terhadap hidrolisis [4]. Kestabilan senyawa kurkumin akan terganggu oleh UV-Vis [5], efek cahaya, pelarut dan oksigen [6], panas [7].…”
Section: Pendahuluanunclassified
“…While numerous studies on the anticancer and other biological properties of curcumin and its metal complexes are reported, the photodynamic effect of metal complexes of curcumin in cancer cells remains unexplored despite curcumin's rich photophysical and photochemical properties [2,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Earlier reports on cobalt (III), oxidovandium(IV), lanthanide(III), copper(II), zinc(II) and Ir(III) complexes have also shown that the hydrolysis of curcumin gets suppressed upon binding to a metal ion [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Using this strategy, we have recently reported an oxo-bridged iron(III) complex of curcumin that shows photocytotoxicity in HeLa and MCF-7 cancer cells in visible light (Luzchem photoreactor, 400-700 nm, 10 J cm-2) [57].…”
Section: Photocytotoxicity Of Curcumin When Bound To Iron (Iii)mentioning
confidence: 99%
“…To improve the aqueous stability and hence therapeutic efficacy of curcumin, several modifications of curcumin have been synthesized and tested. One very recent and successful strategy to address this problem takes advantage of curcumin's metal binding property [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]. Binding of curcumin to a metal ion via its β-diketone moiety significantly reduces the tendency of curcumin to undergo hydrolysis in aqueous medium and hence could result in improved bioavailability and therapeutic efficacy.…”
Section: Introductionmentioning
confidence: 99%